A Profession-Based Learning Approach to Teaching Contemporary Parks and Recreation Students. Issue 1 (3rd July 2021) - Hallmon, Augustus W.; Myllykangas, Susan A.; Nagata, Shinichi
Abstract: Myllykangas postulated that students studying various careers within the parks and recreation profession might prefer a certain learning style, which is, often the case, different from the teaching style used by the faculty. In order to address learning styles of students, it is essential to be able to adapt to the learning styles of each student in the classroom. The Profession-Based Learning model offers a means to connect to the learning styles of students. The Profession-Based Learning model provides students with opportunities to apply the learning that occurs in the classroom with projects and experiences that typically occur within the professional environment. This paper would assist faculty to effectively meet the desired learning styles of contemporary students.